2014
DOI: 10.1016/j.arth.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Comparison of the Orientation of the Transverse Acetabular Ligament and the Acetabulum

Abstract: Aligning the acetabular component with the Transverse Acetabular Ligament (TAL) to ensure optimal anteversion has been reported to reduce dislocation rates. However, to our knowledge in vivo measurement of the TAL angle has not yet been reported in a large cohort of normal hips. CT scans of 218 normal hips were analyzed. The TAL and four acetabular rim anteversion angles were measured (superiorly to inferiorly) relative to the anterior pelvic plane. The mean TAL anteversion angle was 20.5° ± 7.0°, and the acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…We evaluated the operative anteversion of TAL preoperatively using 3D-CT. The average angle of the TAL and variations corresponded to previously reported anatomical, intraoperative, and image evaluation of the TAL [8,9,12,15,20,21]. These findings suggest that our instrumentation using 3D-CT can achieve accurate measured values.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We evaluated the operative anteversion of TAL preoperatively using 3D-CT. The average angle of the TAL and variations corresponded to previously reported anatomical, intraoperative, and image evaluation of the TAL [8,9,12,15,20,21]. These findings suggest that our instrumentation using 3D-CT can achieve accurate measured values.…”
Section: Discussionsupporting
confidence: 66%
“…Archbold et al reported that the transverse acetabular ligament (TAL) and acetabular labrum were useful for determining the anteversion of the acetabular component [7]. TAL has been evaluated as an anatomic landmark for acetabular component orientation [7][8][9][10][11][12][13][14][15][16][17]. The usefulness of TAL as a landmark is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The research questions examine previously reviewed crite- Studies suggest that the rate of dislocation can be reduced to 0.6% by using the TAL as a reference for acetabular cup alignment. 21,22 The position of the cup was also determined to be anteverted, aligned, or retroverted to the native TAL. Using the software, 2 lines were created from the center of the cup to the acetabular edge to form a reference for assigning clock values to (1) where the cup was within bone, (2) where the cup was not inside the bone (Figure 2), and (3) where the lateral most aspect of the acetabulum was.…”
Section: Methodsmentioning
confidence: 99%
“…However, the acetabular transverse ligament is considered to be a factor that limits femoral head reduction in the developmental dislocation of the hip, and its excision and resection release the acetabular entrance, rendering the femoral head easier to reduce to the acetabulum (9,10). The acetabular transverse ligament is easy to visualize, even in the joints with arthritic changes; thus, it is clinically useful (e.g., as an indicator of acetabular component placement in total hip arthroplasty) (11)(12)(13). Ligaments usually connect to bones; however, the transverse ligament also connects to the anterior and posterior angles of the acetabulum.…”
Section: Introductionmentioning
confidence: 99%